Counseling and Screening of Non-Communicable Diseases for the Elderly in the HIMO-HIMO Social Center for the Elderly in Ternate - Ayu Melisa Putri; Nani Supriyatni; Nurfina Karim; Wa Naziroh Salfiani; Andiani; Tati Sumiati; Yusnita; Hestyn Amalia; Sitti Nurhidayanti; Suryadi M. Ali; Monisa A. Hi. Djafar (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
The increase in life expectancy has led to a significant increase in the elderly population in Indonesia, where the proportion reached 11.82% by 2023. The elderly are a vulnerable group to non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and hyperuricaemia, which are the leading causes of morbidity and decreased quality of life. This study aimed to improve elderly knowledge regarding NCDs and identify health risk factors through health education and screening activities. A one-group pretest-posttest design was conducted involving 32 elderly participants at the Himo-Himo Social Institution for the Elderly in Ternate City. Health education was provided, followed by screening for blood pressure, blood glucose, and uric acid levels. Data were analysed descriptively, while differences in knowledge scores before and after the intervention were assessed using a paired sample t-test. The results showed a significant increase in knowledge after the intervention (p = 0.000; t = -4.256). Screening results revealed that 84.4% of participants had elevated systolic blood pressure, indicating a high risk of hypertension, while 75.0% showed abnormal diastolic blood pressure. In addition, 56.3% of participants had elevated blood glucose levels, suggesting a risk of diabetes mellitus, and 71.9% had elevated uric acid levels, indicating hyperuricemia. Health education and NCD screening effectively improved elderly knowledge and facilitated early detection of health problems. These activities are essential and should be implemented routinely as part of preventive and promotive health efforts to improve the quality of life among older adults.